Organic Fertilizer from Animal Waste: A Community-Based Economic Strategy for Sustainable Agriculture - Andini; Mutiara Ramadani; Mutiara Cantika; Rini; Fatimawali; Asriyana S Kaseng (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Datokarama Palu, 2024)
Effective animal waste management remains a persistent challenge in rural communities, often resulting in environmental degradation and economic inefficiencies. This community service program aims to empower local farmers and livestock keepers by promoting the conversion of animal waste (kohe) into organic fertilizer, thereby supporting sustainable and economically viable agricultural practices. Employing a Community-Based Research (CBR) approach, the program incorporated participatory training, technology transfer, and hands-on composting activities to build community capacity in organic fertilizer production. Data were collected through structured surveys, in-depth interviews, and laboratory analysis to assess improvements in knowledge, fertilizer quality, and economic outcomes. The results indicate a significant enhancement in participants’ understanding of waste management, with 75% demonstrating readiness to adopt the technology. Laboratory tests confirmed that the produced organic fertilizer met established quality standards, contributing to reduced reliance on chemical inputs, lower production costs, and improved soil fertility. Furthermore, the initiative stimulated local economic resilience by fostering new agribusiness opportunities. In conclusion, the CBR-driven model effectively integrates environmental sustainability with economic empowerment, offering a scalable and replicable strategy for community-led agricultural development.